Prognostic Relevance of Left Ventricular Global Longitudinal Strain in Patients With Heart Failure and Reduced Ejection Fraction - Chimed Surenjav; Stassen Jan; Galloo Xavier; Meucci Maria Chiara; Knuuti Juhani; Delgado Victoria; van der Bijl Pieter; Marsan Nina Ajmone; Bax Jeroen J. (EXCERPTA MEDICA INC-ELSEVIER SCIENCE INC, 2025)
Patients with heart failure (HF) and reduced ejection fraction (HFrEF) are complex patients who often have a high prevalence of co-morbidities and risk factors. In the pres-ent study, we investigated the prognostic significance of left ventricular (LV) global longi-tudinal strain (GLS) along with important clinical and echocardiographic variables in patients with HFrEF. Patients who had a first echocardiographic diagnosis of LV systolic dysfunction, defined as LV ejection fraction & LE;45%, were selected. The study population was subdivided into 2 groups based on a spline curve analysis derived optimal threshold value of LV GLS (& LE;10%). The primary end point was occurrence of worsening HF, whereas the composite of worsening HF and all-cause death was chosen for the secondary end point. A total of 1,873 patients (mean age 63 12 years, 75% men) were analyzed. During a median follow-up of 60 months (interquartile range 27 to 60 months), 256 patients (14%) experienced worsening HF and the composite end point of worsening HF and all-cause mortality occurred in 573 patients (31%). The 5-year event-free survival rates for the primary and secondary end point were significantly lower in the LV GLS & LE;10% group compared with the LV GLS >10% group. After adjustment for important clinical and echocardiographic variables, baseline LV GLS remained independently asso-ciated with a higher risk of worsening HF (hazard ratio 0.95, 95% confidence interval 0.90 to 0.99, p = 0.032) and the composite of worsening HF and all-cause mortality (hazard ratio 0.94, 95% confidence interval 0.90 to 0.97, p = 0.001). In conclusion, baseline LV GLS is associated with long-term prognosis in patients with HFrEF, independent of various clinical and echocardiographic predictors.